Investigating Band Gap Energy of Quantum Doped Semiconductors - Ahmed Marwan Abdelrahman Foda (2013)
Abstract
Contents
Thesis (M.A.)$1 (BNile University, Egypt, 2013 .s
"Includes bibliographical references"
Text in English, abstracts in English.
Keywords: Nano- Science & Technology; Dissertation, Academic